1986
DOI: 10.1148/radiology.158.1.3940387
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease: gated MR imaging in 72 patients.

Abstract: Seventy-two patients (aged 2 months to 75 years; mean 23 years) with a variety of congenital anomalies of the heart and great vessels underwent ECG-gated magnetic resonance (MR) imaging using the multisectional spin-echo technique (0.35 Tesla). The ability to define segmental anatomy and intracardiac anomalies on transverse, sagittal, and coronal images was evaluated. MR images were graded as excellent, diagnostic, or nondiagnostic, and MR findings were corroborated by angiography and/or two-dimensional echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Therefore the evaluation of shunting procedures usually requires invasive procedures like angiography. Recent articles have emphasized the role played by MRI in demonstrating cardiac anomalies [2,3]. Previously published extensive series have been restricted to adults and young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the evaluation of shunting procedures usually requires invasive procedures like angiography. Recent articles have emphasized the role played by MRI in demonstrating cardiac anomalies [2,3]. Previously published extensive series have been restricted to adults and young children.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobstein et al reported successful imaging in 11 of 17 angiographicaUy controlled shunts [1]. Didier et al mentioned that MR imaging accurately assessed 4 Blalock-Taussig shunts included in a series of 15 postoperative congenital heart patients [2]. More recently Katz et al included 18 systemic-pulmonary shunts in a series of mediastinal vessel postoperative evaluations (27 patients -age ranging from 11 months to 37 years) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis with horizontal and frontal images of MRI defined the segmental anatomy, state of the ventricular and atrial septa and position of the great vessels [4,7]. These images were especially useful in the recognition of the spatial relationships of the cardiac segments.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effectiveness of magnetic resonance imaging (MRI) in diagnosing complex congenital cardiac anomalies has been reported [2,5,9] . Although for newborns and infants, in whom the target region is very small, MRI is not currently appropriate, since the slice is too thick, spatial resolution is poor, and examination time is too long, the new continuous-rotation CT has excellent diagnostic capabilities, even with newborns and infants .…”
Section: Discussionmentioning
confidence: 99%